Encouraging French medical students to choose a career in psychiatry: How and why?. (August 2013) - Andlauer, Olivier; Van Effenterre, Aude; Haffen, Emmanuel; Sechter, Daniel; Farooq, Kitty; Lydall, Gregory; Malik, Amit; Bhugra, Dinesh
Abstract There is an increasing demand for psychiatrists in France. This paper reviews the reasons for French medical students choosing psychiatry and the rationale and mechanisms for encouraging them towards this medical speciality. The main factors associated with choosing psychiatry as a career are the quantity and quality of undergraduate training and placements in psychiatry, better attitudes towards psychiatry and more emphasis on a positive life/work balance. The quality of postgraduate training can also influence students' decisions. Medical students should be encouraged to choose psychiatry first to counterbalance the existing stigma towards mental illness within the society, but also towards psychiatry within the medical profession, and second because of the current decline in French medical demography. Ways to improve recruitment are a selection process that favours a large number of psychiatric trainees, and an increase in the quality and quantity of training. Providing medical students with relevant information about training in psychiatry, notably through a national trainees' association, will not only improve the quality of care by increasing recruitment in psychiatry, but also ensure that all future doctors are familiar with and develop positive attitudes towards mental health issues.